LIKUIFASI ENZIMATIK β - KAROTEN SEBAGAI FUNCTIONAL FOOD YANG TERDAPAT DALAM POMACE DARI BUAH LABU KUNING - Santosa Herry; Kusumayanti Heny (TEKNIK, 2012)
Attempts to separate the β carotene contained in pomace or pulp byproduct pumpkin fruit juicing process(Cucurbitae moschata) is potential. The magnitude of benefit of β-carotene as a chemo preventive, high contentof β-carotene in pumpkin, strong pumpkin fruit shelf life and high content of β-carotene in the pomace, an initialconsideration of this research. β-Carotene enzmatik liquefaction using pectinase enzyme combination (P) andcellulose (C), subject to the pomace. liquefaction / hydrolysis carried out in a stirred tank reactor to determine:the most influential variable ratio between enzyme ratio P: C; temperature and pH. Influential process variableswas determined using two-level factorial design method Quicker. From the experimental results of the data if itis known that the degree of acidity of pH is the single most influential variable in the process of β-caroteneliquefaction presents in pumpkin fruit pomace.